FINANCIAL SYSTEM AND THE LOCAL GOVERNMENT IN EUROPEAN COUNTRIES - Teki Kurti (European Scientific Journal, ESJ, 2014)
Local governing represents the first election school in the formation of the bodies and institutions that are closer to the governed, that in it carry the greatest and aware interest of the governed. It observes the basic functioning of the financial system, the creation and realization of the relations between the government and the governed, through which are implemented the basic principles of: - participation in governance; -expression of the will and liking of governing; - fulfilment of tasks of governing according to the interests and aspirations of the governed; - responsibility and accountability of the government. The effectiveness of the government, assessed through the fulfilment of tasks with concrete results related to the fulfilment of the interests of the entire nation and society, is another important aspect in the system of governing. In fact one of the directions of the two definitions of local Autonomy is to realize an independent school to provide financial support, in the management of incomes and spending too.